PENGARUH MEDIA BALOK TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK KELOMPOK A TK MUTIARA BANGSA SURABAYA - Astri Merdian Putri; Aulia Insani; Isabella Hasiana (PERNIK, 2022)
This research was conducted on group A children in Mutiara Bangsa Surabaya Kindergarten which is motivated by the cognitive development of children in recognizing geometric shapes is still not optimal, this is because the teacher is not optimal in utilizing the use of media blocks to develop children's cognitive abilities .This research method is quantitative pre-experimental with One Group Pretest-Possttest Design. The subjects in this study were 30 children in group A. Data analysis techniques in this study, using the t test technique and calculations through SPSS. Â The statistical test in this study is to test whether the media beam influences the ability to recognize geometric shapes in children of group A TK Mutiara Bangsa Surabaya. Then from the results of the calculation of t test through SPSS. Obtained Sig (0,000) < 0.05. So, the conclusion of this study is that there is an effect of the beam media on the ability to recognize geometric shapes in children of group A TK Mutiara Bangsa Surabaya